2003
DOI: 10.1191/1352458503ms939oa
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain in a large community sample of persons with multiple sclerosis

Abstract: Approximately a fourth of this sample described having a chronic pain problem characterized by severe pain intensity and significant pain-related interference with activities. Disability due to pain may be more important than previously recognized for the MS population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
165
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(188 citation statements)
references
References 31 publications
18
165
2
3
Order By: Relevance
“…Some previous studies have reported that MS-related disability is associated with pain, 3,6 whereas others have found no association. 34,35 Possible explanations for conflicting findings include vast differences in sample sizes (with larger, survey studies more likely to find significant associations), different aspects of pain explored (acute pain, chronic pain, experience of any pain, frequency, intensity, or pain interference), different instruments used to measure different aspects of pain, and differences in how MS-related disability is measured (clinical examination or self-report).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Some previous studies have reported that MS-related disability is associated with pain, 3,6 whereas others have found no association. 34,35 Possible explanations for conflicting findings include vast differences in sample sizes (with larger, survey studies more likely to find significant associations), different aspects of pain explored (acute pain, chronic pain, experience of any pain, frequency, intensity, or pain interference), different instruments used to measure different aspects of pain, and differences in how MS-related disability is measured (clinical examination or self-report).…”
Section: Discussionmentioning
confidence: 85%
“…3,4 Pain often interferes with activities of daily living and sleep, compromising occupational and social roles for many. 5,6 People experience various types of pain, including central neuropathic pain (eg, dysesthetic extremity pain, tonic muscle spasm, or trigeminal neuralgia), musculoskeletal pain (such as low back pain), or mixed neuropathic and nonneuropathic forms of pain (eg, headaches).…”
mentioning
confidence: 99%
“…Osterberg et al (45) surveyed 364 patients registered in their multiple sclerosis clinic and found that 27.5% had central pain, including almost 5% with trigeminal neuralgia. Most of the time the pain was severe, occurred daily, lasted years and was rated by the patients as a heavy burden (46).…”
Section: Multiple Sclerosismentioning
confidence: 99%
“…Participants were selected from a sample of community-dwelling persons with MS who had previously been contacted through the Multiple Sclerosis Association (MSA) of King County, Washington, USA, as part of a survey that assessed a variety of symptoms and other aspects of living with MS [26][27][28] and who indicated that they were interested in being contacted in the future regarding additional research studies. A consent form and a cover letter inviting the potential study participants to participate in the study accompanied each survey.…”
Section: Sample Populationmentioning
confidence: 99%